Fibrinogen and fibrin induce synthesis of proinflammatory cytokines from isolated peripheral blood mononuclear cells - Jensen, Torstein; Kierulf, Peter; Sandset, Per M.; Klingenberg, Olav; Joø, Gunn B.; Godal, Hans C.; Skjønsberg, Ole H. (Thrombosis and Haemostasis, 2007)
Fibrinogen in plasma includes three main fractions; high-molecular- weight (HMW) -fibrinogen, low-molecular-weight (LMW) -fibrinogen, and very-low-molecular-weight (LMW`) -fibrinogen. During acute-phase conditions, plasma fibrinogen levels and the HMW-/LMW-fibrinogen ratio increase rapidly due to increased synthesis of HMW-fibrinogen. The consequences of elevated plasma fibrinogen levels and local deposition of fibrin in inflammatory tissues observed during acute-phase conditions are not clear.We wanted to investigate proinflammatory effects of fibrinogen and fibrin on peripheral blood mononuclear cells (PBMC) as reflected by altered mRNA expression and synthesis of the proinflammatory cytokines IL-6,TNF- α and IL-1 β, and to explore the significance of altered HMW-/LMW-fibrinogen ratio. PBMC were isolated from whole blood using Lymphoprep® . HMW-fibrinogen was separated from unfractioned fibrinogen by ammonium sulphate precipitation. Cells were incubated with unfractioned fibrinogen, HMW-fibrinogen or fibrin. Cytokine levels in cell lysates were determined using ELISA assays. Real-time PCR was used for mRNA quantification. We found that fibrinogen significantly increased mRNA levels, and induced synthesis of the proinflammatory cytokines IL-6 and TNF- α in PBMC in a dose dependent manner. Median (25, 75 percentile) IL-6 and TNF- α concentrations were 12 (5, 40) pg/ ml and 16 (0,61) pg/ml,respectively.Median mRNA quantity was increased 12.3– (6.6, 48.6) and 1.7– (1.5, 6.5) fold for IL-6 and TNF- α compared to controls.The stimulatory effect of unfractioned fibrinogen was not significantly different from HMW-fibrinogen. Fibrinogen and fibrin were equally effective in promoting cytokine synthesis from PBMC.The results support that fibrin and fibrinogen may actively modulate the inflammatory process by inducing synthesis of proinflammatory cytokines from PBMC.
Keywords: Fibrinogen; fibrin; PMBC; inflammation; cytokines